ЗОЛОТО – ПЛАТИНОНОСНОСТЬ ГЛАВНЕЙШИХ ТИПОВ ЖЕЛЕЗОРУДНЫХ ФОРМАЦИЙ МИРА (ИНФОРМАЦИОННО -АНАЛИТИЧЕСКИЙ ОБЗОР) - Чернышов Н.М.; Молотков С.П.; Резникова О.Г. (My University, 2003)
A brief informational and analytical overview of gold and platinum content of ore deposits differing in formation, commercial and genetic features, resources and reserves, including magmatic, contact-metasomatic, crusts-of-weathering and metamorphic, is presented. Prominence is given to the problem of gold and platinum content in large and unique deposits of ferruginous quartzites, providing over 60% of the world's iron production and containing independent mineral phases of Au, Pt, Pd, Os, Ru and Ir. Together with technogenic products of their processing they represent a new, unique in resources, non-traditional source of noble metals in the XXI century.
Keywords: ГЛАВНЕЙШИЕ ТИПЫ ЖЕЛЕЗОРУДНЫХ ФОРМАЦИЙ МИРА; ЗОЛОТО - ПЛАТИНОНОСНОСТЬ; 549.2./.8:553.3/.4:553.491.8.04